(untitled) (Research, Society and Development, 2022)
The object of study of this research are active methodologies from the perspective of Professional and Technological Education, which is an approach to the evolution of the educational identity of work in light of the market sense historically acquired through the process of capitalist development, as well as on education and its transformations throughout history, analyzing its changes and highlighting the unveiling of the current Brazilian educational project. This study is qualitative in nature, as a research that arises from the impossibility of understanding, through numerical data, phenomena linked to intuition and subjectivity, therefore, it does not need a numerical structure to analyze it, however, which produces a huge amount of narrative data. Thus, our analysis will be based on the investigation of data found in the selected documents. Considering that the conceptual bases of professional and technological education defend a comprehensive human education, with perspectives of unilateralism, it is important to understand the subject as a whole, that is, a subject who is not trained only for the labor market, but who have the possibility of a link between education and work.